Implementation of National Defense in the Technology Era in Civic Education Learning - Denryas, Raissha Ardellia (International Journal of Students Education, 2024)
Defending the country and national resilience are attitudes that every citizen must have. The younger generation, as the successors of the nation, needs to be well prepared so that they can contribute to the progress of the country. Defending the country has an important role in achieving the goals of a country. In the 1945 Constitution, Article 27 and Article 30 paragraph (1) regulate the rights and obligations of every citizen in efforts to defend the country and national security defense. Therefore, it is important to instill and implement an attitude of defending the country, especially among the younger generation through civic education. Amidst technological advances that have a negative impact on national resilience and reduce the sense of defending the country among millennials, the challenges that will be faced in the future are increasingly diverse and complex. Thus, the attitude of defending the country and its application in everyday life becomes very important. This article will discuss the results of research on the implementation of defending the country in Civic Education learning. In addition, this article will also explain the activities of defending the country that need to be implemented at various levels of education, from elementary school to college. The material in this work can be used as a reference for the development of curriculum, regulations, and policies related to defending the country.